Strategi Komunikasi Antarbudaya Pasangan Suami Istri Kawin Campur Eropa - Indonesia Di Kota Makassar - Maesurah, Sitti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Mixed marriages are a result of intercultural interaction. This sacred process not only binds two individuals but also brings together two very different cultures. Therefore, an effective intercultural adaptation is needed as an effort to understand life partners, so that misunderstandings that lead to disharmony and conflicts can be avoided. This study is to analyze the intercultural adaptation process carried out by the wife who is an Indonesian citizen and the husband who comes from various countries in the Continent of Europe who are involved in mixed marriages in Makassar City. This research uses descriptive qualitative method with a case study approach. The results showed that there were four stages of adaptation carried out by mixed European-Indonesian married couples. In addition, it was found that intercultural adaptation plays a major role in maintaining the harmony of mixed marriages. Keywords: Intercultural Adaptation, Married Couples, Mixed Marriage